Corrigendum to “Taxonomic studies in the Aganisia complex (Orchidaceae, Zygopetalinae)” - Meneguzzo, Thiago E. C.; Berg, Cássio Van Den (Phytotaxa, 2016)
We propose Aganisia cyanea f. albiflora as a new name for Acacallis cyanea f. alba because our previously proposed Aganisia cyanea f. alba was an illegitimate homonym of Aganisia cyanea var. alba, a taxon currently recognized as Warreella cyanea f. alba.